Analisis Strategi Daya Saing Pasar Tradisional Dan Modern Berdasarkan Minat Pembelian Pengunjung - Endrianto Sahedtyo Nugroho Suhadak; Agung Dwi Nugroho (JURNAL ILMIAH EKONOMI DAN MANAJEMEN, 2025)
The development of the trade sector shows that there is increasingly strong competition between modern markets and traditional markets in attracting consumer attention. This study aims to analyze the differences between the two based on the perspective of visitors on purchasing power. The method used is a qualitative descriptive approach through direct observation and interviews. The results of the study revealed that traditional markets stand out in terms of local culture and social closeness between sellers and buyers. Meanwhile, modern markets are preferred by consumers who prioritize convenience, product diversity, and modern facilities. Digital marketing factors, product innovation, and market image also play an important role in influencing consumer purchasing interest in each type of market.